2019
DOI: 10.1002/dc.24366
|View full text |Cite
|
Sign up to set email alerts
|

CD15, CD30, and PAX5 evaluation in Hodgkin's lymphoma on fine‐needle aspiration cytology samples

Abstract: Background: The phenotypical identification of diagnostic cells is crucial for the diagnosis of Hodgkin's lymphoma (HL) on fine-needle aspiration cytology (FNAC). The aim of this study is to evaluate the immunocytochemical (ICC) expression of CD30, CD15, and PAX5 in Hodgkin's cells (HC) and Reed-Sternberg cells (RSC) on smears and cell-blocks (CB) of HL and to compare the performance of each antibody on smears and CB.Methods: In 21 FNAC cases of histologically confirmed classical HL, ICC identification of HC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Cytopathological expression of CD15 occurs in 66,7% of cases. In addition, CD15 resulted to be more effective on smears and cell blocks [84]. CD15 can also be detected as being stained using autoclave and microwave.…”
Section: Experimental Medicine Involving Cd15mentioning
confidence: 98%
“…Cytopathological expression of CD15 occurs in 66,7% of cases. In addition, CD15 resulted to be more effective on smears and cell blocks [84]. CD15 can also be detected as being stained using autoclave and microwave.…”
Section: Experimental Medicine Involving Cd15mentioning
confidence: 98%
“…The biological material will then be available for molecular tests. Similarly, the only smear suitable for molecular tests may be stained with immunocytochemistry (most often with hematoxylin and diaminobenzidine) [79][80][81]. Among all the cases included in the present review, only one diaminobenzidine-stained slide was tested as input for the Idylla EGFR system, and it resulted in a false negative result [66].…”
Section: Performance On Different Cytological Samplesmentioning
confidence: 99%
“…In addition, a previous work described that PAX5 could be a useful marker in the diagnosis of HL with atypical immunophenotypic characteristics, although in cHL, PAX5 expression may be weaker [ 24 ]. In contrast, several studies have reported that the expression of PAX5 ranges from 88–100% in patients with cHL [ 25 , 26 , 27 , 28 ]. However, the reason for this large range of PAX5 expression could not be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, double immunodetection was performed, finding that there was no nuclear colocalization of the proteins studied. With this, we demonstrated that although PAX5 expression occurred, it was not sufficient to inhibit NOTCH1 expression and that the translation of the protein is inhibited by different mechanisms, such as aberrant activation of the NOTCH pathway, which is a regulator of the activation of the NF-kB signaling pathway and has anti-apoptotic activity in RS cells [ 28 ]. Additionally, at the same time, it activates the NOTCH1 receptor, which inhibits the expression of B genes.…”
Section: Discussionmentioning
confidence: 99%